RELATIONSHIP BETWEEN ROLLING AND SLIP RESISTANCE IN ROLLING BEARINGS - Bondarenko, L. M.; Babyak, M. O.; Yakovlev, S. O.; Istin, S. O.; Moskalev, G. Yu. (Science and Transport Progress, 2016)
Purpose. About one of the causes of slip rolling is known from the second half of the 19th century, it was believed that the slip resistance appears at the place of contact due to different speeds on the arc of contact. Only in the mid-20th century it was proved that this resistance is negligible in rolling resistance. However (for some unknown reason) it is ignored the fact that in practice in rolling bearings may rotate both the inner ring with a stationary outer one, and vice versa almost in equal relations. It is not taken into account the fact that the ball or roller in the rolling bearings runs the different distance along the roller path of the outer and inner bearing cages in one revolution. This fact is not taken into account in determining the calculated values for the friction coefficient of a rolling bearing reduced to the shaft. Therefore, the aim of this work is to determine the influence of path length on the track riding the outer and inner race of the bearing on the determination of the calculated value of the coefficient of friction of rolling bearings is given to the shaft. Methodology. The solution technique is based on the theory of plane motion of a rigid body, the theory of Hertzian contact deformation and the analytical dependencies for determination of coefficient of rolling friction. Findings. The obtained dependences on determination of rolling resistance of the balls or rollers along the bearing tracks of inner and outer bearing cages as well as path difference metering of the rolling on them allows to analytically obtain the rolling resistance and slipping for any size of bearings and different devices of bearing units. It is also possible at the design stage of rolling nodes to handle not only the design but also the content of the node. Originality. Using the analytical dependences for determination of the rolling resistance of bodies at point and line contacts, and also account for the difference in the path of the rolling ball or roller on the outer and inner cages of the bearing one can more accurately find the rolling resistance in the bearings. Practical value. The obtained dependences allow designing the bearing units with minimal energy consumption.